Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve for the zeros of the function [tex]\( h(x) = (x^2 - 49)(x + 4) \)[/tex], we follow these steps:
1. Set the function equal to zero:
[tex]\[ (x^2 - 49)(x + 4) = 0 \][/tex]
2. Factorize [tex]\( x^2 - 49 \)[/tex]:
We recognize that [tex]\( x^2 - 49 \)[/tex] is a difference of squares, which can be factored as:
[tex]\[ x^2 - 49 = (x - 7)(x + 7) \][/tex]
3. Substitute the factored form back into the equation:
[tex]\[ (x - 7)(x + 7)(x + 4) = 0 \][/tex]
4. Find the roots by setting each factor equal to zero:
[tex]\[ x - 7 = 0 \quad \Rightarrow \quad x = 7 \][/tex]
[tex]\[ x + 7 = 0 \quad \Rightarrow \quad x = -7 \][/tex]
[tex]\[ x + 4 = 0 \quad \Rightarrow \quad x = -4 \][/tex]
Thus, the zeros of the function are [tex]\( x = 7 \)[/tex], [tex]\( x = -7 \)[/tex], and [tex]\( x = -4 \)[/tex].
Among the provided answer choices:
- A. 0 is not a zero of [tex]\( h(x) \)[/tex].
- B. 4 is not a zero of [tex]\( h(x) \)[/tex].
- C. 7 is a zero of [tex]\( h(x) \)[/tex].
- D. 49 is not a zero of [tex]\( h(x) \)[/tex].
Therefore, the correct answer is:
C. 7
1. Set the function equal to zero:
[tex]\[ (x^2 - 49)(x + 4) = 0 \][/tex]
2. Factorize [tex]\( x^2 - 49 \)[/tex]:
We recognize that [tex]\( x^2 - 49 \)[/tex] is a difference of squares, which can be factored as:
[tex]\[ x^2 - 49 = (x - 7)(x + 7) \][/tex]
3. Substitute the factored form back into the equation:
[tex]\[ (x - 7)(x + 7)(x + 4) = 0 \][/tex]
4. Find the roots by setting each factor equal to zero:
[tex]\[ x - 7 = 0 \quad \Rightarrow \quad x = 7 \][/tex]
[tex]\[ x + 7 = 0 \quad \Rightarrow \quad x = -7 \][/tex]
[tex]\[ x + 4 = 0 \quad \Rightarrow \quad x = -4 \][/tex]
Thus, the zeros of the function are [tex]\( x = 7 \)[/tex], [tex]\( x = -7 \)[/tex], and [tex]\( x = -4 \)[/tex].
Among the provided answer choices:
- A. 0 is not a zero of [tex]\( h(x) \)[/tex].
- B. 4 is not a zero of [tex]\( h(x) \)[/tex].
- C. 7 is a zero of [tex]\( h(x) \)[/tex].
- D. 49 is not a zero of [tex]\( h(x) \)[/tex].
Therefore, the correct answer is:
C. 7
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.